Profil Lipid dan Gambaran Histopatologi Aorta Tikus Hiperlipidemia dengan Pemberian EKSTRAK Kopi Hijau - Fransiska Maria Christianty; Diana Holidah; Fifteen Aprila Fajrin; Monica Cinuradha Aura Salsabina; Andrean Roni (Fakultas Farmasi Universitas Pancasila, 2020)
The high prevalence and risk of death from cardiovascular disease has led to the development of alternative treatments derived from nature. Green coffee has not undergone a roasting process. The product is claimed as a weight loser, even though the cardiovascular effects are still controversial. This study aim was to determine the impact of green coffee bean extract on rat lipid profiles and aortic histopathology. Green coffee bean extract made by a re-maceration method using 96% ethanol. Rats were induced with high-fat diet then treated with green coffee bean extract at a dose of 200; 400; and 800 mg/kg BB. Rats were sacrificed, blood was taken for lipid profile measurements and observations were made on histopathological preparations of rat aorta. The results showed that administration of green coffee bean extract (especially doses of 200 mg/kg BW) for 14 days in hyperlipidemic mice could significantly improve lipid profiles, except HDL levels. Microscopic observations showed that green coffee bean extract could enhance the rat aorta histopathology even though it did not match normal conditions. We can conclude that green coffee bean extract has potential effects to be developed as an alternative to traditional medicine that has antihyperlipidemic effects and cardiovascular protective effects.